Epilepsia motor menor - Pascual Gispert, Joaquín; Gueller Konski, José; Carpio Sabateña, Roberto; Guzmán Rodríguez, Enrique; Pelayo González Otto, Eduardo; Machado Fernández, V. (Revista Cubana de Pediatría, 2023)
Describe los tipos de ataque del motor menor